HUBUNGAN PENDIDIKAN DAN PENDAPATAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SD NEGERI 105268 TELAGA SARI - Effendi Manalu (Universitas Negeri Medan, 2016)
Abstract: The Relationship Of Education And Parent's Revenue To The Motivation Of Learning Of Elementary School Students Of State Elementary School 105268 Telaga Sari. This study aims to: (1) Know the relationship between parent education with student learning motivation. (2) to know the relation between parent income with student learning motivation. (3) to know the relation between education and parent income to student learning motivation. The research used quantitative descriptive method. The sample of the study amounted to 33 people. Technical analysis of data using correlation statistics and multiple regression. The results showed that: (1) There was no positive correlation and significance between education and learning motivation of elementary school students 105368 Telaga Sari. Shown by coefficient korelasir_x1y = 0,114 and obtained t_hitung equal to 0,64 with regression equation Y '= 77,143 + 2,003 X_1 (2) There is a positive and significant correlation between parent income to motivation learn student of Elementary School 105268 Telaga Sari. Shown by correlation coefficient r_x2y = 0,472 and obtained t_hitung equal to 2,97 with regression equation Y '= 69,426 + 2,004 X_2 (3) There is a positive relationship and significance between education and income of parent to student learning motivation SD Negeri 105268 Telaga Sari. Indicated by double correlation coefficient r_x1x2y = 0.482 and obtained F_count of 4,546 with multiple regression equation Y '= 64,625 + 1,753 X_1 + 1,992 X_2. The result of determination coefficient analysis (R ^ 2) between education and parent income on student learning motivation equal to 0,233 or 23,3%. Keywords: Education, Parents Income, Student Motivation Abstrak: Hubungan Pendidikan Dan Pendapatan Orang Tua Terhadap Motivasi Belajar Siswa SD Negeri 105268 Telaga Sari. Penelitian ini bertujuan untuk : (1) Mengetahui hubungan antara pendidikan orang tua dengan motivasi belajar siswa. (2) Mengetahui hubungan antara pendapatan orang tua dengan motivasi belajar siswa. (3) Mengetahui hubungan antara pendidikan dan pendapatan orang tua terhadap motivasi belajar siswa. Penelitian menggunakan metode deskriptif kuantitatif. Sampel penelitian berjumlah 33 orang. Teknis analisis data menggunakan statistik kolerasi dan regresi ganda. Hasil penelitian menunjukkan bahwa: (1) Tidak terdapat hubungan yang positif dan signifikansi antara pendidikan terhdap motivasi belajar siswa SD Negeri 105368 Telaga Sari. Ditunjukkan oleh koefisien korelasi = 0,114 dan diperoleh sebesar 0,64 dengan persamaan regresi Y’= 77,143 + 2,003 (2) Terdapat hubungan yang positif dan signifikan antara pendapatan orang tua terhadap motivasi belajar siswa SD Negeri 105268 Telaga Sari. Ditunjukkan oleh koefisien korelasi = 0,472 dan diperoleh sebesar 2,97 dengan persamaan regresi Y’ = 69,426 + 2,004 (3) Terdapat hubungan yang positif dan signifikansi antara pendidikan dan pendapatan orang tua terhadap motivasi belajar siswa SD Negeri 105268 Telaga Sari. Ditunjukkan oleh koefisien kolerasi ganda = 0,482 dan diperoleh sebesar 4,546 dengan persamaan regresi ganda Y’ = 64,625 + 1,753 + 1,992 . Hasil analisis koefisien determinasi () antara pendidikan dan pendapatan orang tua terhadap motivasi belajar siswa sebesar 0,233 atau 23,3%. Kata Kunci : Pendidikan, Pendapatan Orang Tua, Motivasi Belajar Siswa